Glycolipid nanoparticles target the spleen and detarget the liver without charge - Kara Gentry; Liming Lian; Hyejin Kim; Ozgenur Celik; Camille Jones; Ananda R. Podilapu; Avraham Shakked; David Loughrey; Ryan Zenhausern; Bora Jang; Jessie Doan; Sebastian Rudden; et al. (Proceedings of the National Academy of Sciences, 2025)
Lipid nanoparticles (LNPs) formulated with a neutral helper lipid can deliver RNA to the liver in humans. However, clinically relevant delivery to other tissues has remained challenging. To avoid the liver, scientists often add antibodies or helper lipids with a permanent charge. Here, we report an alternative approach: antibody- and charge-independent liver detargeting. Using DNA barcoding to test 109 chemically distinct LNPs in vivo, we found that replacing a neutral helper lipid with a neutral glycolipid reduced liver delivery and increased splenic delivery. Consistent with this differential tropism, these glycolipid nanoparticles caused differences in downstream cellular signaling in vivo compared to traditional LNPs. These data suggest that extrahepatic LNPs can be designed without the imposition of a net negative or positive charge.